CHALLENGES IN IMPLEMENTING SHARIA PRINCIPLES IN THE OPERATIONS OF ISLAMIC BANKS: MANAGERIAL AND CUSTOMER PERSPECTIVES - Siti Munfaqiroh; Bunyamin; Ratri Buda Nugrahanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Islamic banking has gained significant importance in the global financial landscape due to its unique foundation based on Sharia principles. The implementation of these principles within the operational framework of Islamic banks presents several challenges that need to be addressed to ensure compliance with Sharia law while maintaining financial efficiency and customer satisfaction. This study explores the challenges faced by Islamic banks in implementing Sharia principles from both managerial and customer perspectives. Using a qualitative approach, the study involves interviews with bank managers and customers of Islamic banks in Indonesia. The findings indicate that despite the growing demand for Islamic banking services, the challenges in implementing Sharia principles include issues related to regulatory compliance, employee training, product innovation, customer awareness, and the interpretation of Sharia guidelines. Managers often face difficulties in aligning operational strategies with Sharia requirements, while customers struggle with understanding the difference between conventional and Islamic banking products. This study offers insights into how Islamic banks can address these challenges through better managerial practices, enhanced customer education, and the development of more innovative Sharia-compliant products. By examining both managerial and customer perspectives, the research provides a comprehensive understanding of the barriers that hinder the effective implementation of Sharia principles in Islamic banking operations.